FDM-Dienste und -Infrastrukturen – Chancen nur im Verbund? Bericht zur Podiumsdiskussion auf der BiblioCon 2023 - Cyra, Magdalene; Fingerhuth, Matthias; Stegemann, Jessica (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2024)
Services in the field of research data management have increasingly become part of university libraries’ portfolio. A panel discussion at the 2023 BiblioCon in Hannover focused on how libraries can cooperate in this field. In doing so, the discussion also touched on what role libraries can take as a provider of services surrounding research data.
Keywords: Open Science; Research data management; Research support services